FREQUENCY OF SPONTANEOUS BACTERIAL PERITONITIS IN ASYMPTOMATIC PATIENTS WITH CIRRHOTIC ASCITES. : J Peop Univ Med Health Sci. 2025:15(3) 87-92. http://doi.org/10.46536/jpumhs/2025/15.03.662 - Nausheen Ali1, Sultan Ahmed Chandio2, Sumaira Zafar3, Hakim Ali Abro4, Hoat Ali5, Ashfaq Ahmed Bhutto6. (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: Spontaneous bacterial peritonitis (SBP) is a serious intra-abdominal infection that commonly occurs in patients with cirrhotic ascites. Although it is usually seen in symptomatic patients, its frequency in asymptomatic patients with cirrhotic ascites remains a topic of clinical interest, as it can go unrecognized, thus increasing the risk of complications. OBJECTIVE: To identify the prevalence of asymptomatic spontaneous bacterial peritonitis in patients with cirrhotic ascites. To proponent timely detection and enhance clinical outcome via treatment.METHODOLOGY: A cross-sectional studywas conducted at Department of Medicine, Chandka Medical College Hospital, SMBBMU Larkana and 154 patients was enrolled in their first visit between 2024 and January 2025. Totally, 154 cirrhotic consecutive patients aged 18–65, ascites patients but no spontaneous bacterial peritonitis symptoms were enrolled. Following obtaining informed consent, the abdominal paracentesis was executed. Ascitic fluid was studied for PMN count and culture result. Data was analyzed using SPSS version 25. RESULTS: Of 154 patients, 39 (25%) were found to have asymptomatic Spontaneous bacterial peritonitis by increased PMN and positive fluid culture. Culture positivity was shown in 20(51%) with E. coli being most common organism isolated (60%). Majority of the patient were in Child-Pugh B stage (63.6%). CONCLUSION: Twenty-fivepercent of patients with ascites had asymptomatic Spontaneous bacterial peritonitis. Routine diagnostic paracentesis should be done in all such patients whether symptoms is present or not so to reduce morbidity & mortality.